Topical quercetin gel application improved wound healing in Wistar rats (Annals of Medical Research, 2021)
Aim: Quercetin is an antioxidant agent with proven beneficial effects in preventing inflammation. Aim of present study was to evaluate effects of quercetin gel on a secondary intention wound healing model in Wistar rats.Material and Methods: 42 Wistar rats were divided into two groups, one group administered quercetin gel (Q, n=18) while other administered vehicle (C, n=24). 5-mm diameter palatal wounds were created in each rat and all rats were given either quercetin gel or vehicle daily until sacrification days. Gel contained 5% quercetin, 5% benzocaine and glycerin, and each rat administered 0.2 ml of gel every day. Rats were sacrificed at 0th day, 7th day, 14th day, and 21st day. Fibroblast cell counts and inflammatory cell infiltration were evaluated on hematoxylin-eosin stained sections. Collagen type I and III were evaluated via immunohistochemistry.Results: Wound area decreased from day 0 to day 21 in both groups. Significant differences in wound contraction and unhealed wound area were observed between 7th and 21th days in both groups. Improvement in wound area in morphological measurements was similar in both quercetin and control groups except for 21st day on which quercetin exhibited higher wound closure. Histological findings showed significantly higher fibroblast cell counts on 7th, 14th, and 21st days in the quercetin group and difference in both quercetin. Inflammatory cell counts significantly decreased from day 0 to 21 in both groups. Collagen I synthesis were lowest on the 0th day and significantly increased on all other times in both groups. As for collagen III, the levels were highest on 7th day in both groups and significantly decreased on the 14th and 21st day. Conclusion: Present results revealed an improvement in wound healing after quercetin administration which was indicated by decreased inflammatory cells and increased fibroblast cells. However, collagen synthesis was found similar.
Keywords: Antioxidants; collagen; quercetin; wound healing.